PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN TINDAK PIDANA PERKOSAAN - Teguh Prilianto; Philips A. Khana; Adhi Wibowo (UNES Journal of Swara Justisia, 2019)
The crime of rape of a child is part of a sexual crime, provided for in act No. 35 of 2014 on Amendment to act No. 23 of 2002 on Child Protection, which in the law regulates about sexual intercourse committed against children is contained in clause 81. Cases of child intercourse is one of the cases that became the scourge for the community and entered the stage of concern, because every day the crime rape involving children as victims we often hear and we know from various mass media. This happens not only in the school environment, home environment (neighbors), even in the family environment.Based on the above background, the authors formulate the problem as follows: First, how the implementation of legal protection for children victims of criminal rape in Polres Solok Kota? Second, what are the constraints faced in implementing legal protection for child victims of crime of rape and how to overcome these obstacles by Polres Solok Kota?The research that the authors do is an analytical descriptive study that describes the data as it is to then performed an analysis of the data based on relevant rules. The approach method used is the normative juridical approach that is a study that emphasizes or refers to the legal norms contained in legislation relating to diversion. This approach is also supported by an empirical juridical approach, namely by looking at how legislation is applied in field practice. The data source used is primary data and secondary data. The data obtained were analyzed qualitatively and presented in analytical descriptive form.Based on the results of research and discussion, it can be concluded that the legal protection provided by the investigators Polres Solok Kota in the form of the application of criminal provisions in accordance with the law of child protection and attention to the rights of children, providing easy access to information about the development of the case, public and safety assurance to child victims. The obstacles encountered by Solok Kota police investigators are first, from the victim's own children who feel shame, trauma and fear, overcome by providing understanding and assistance by parents / guardians / trusted people during the examination. Secondly, from uncooperative family side, so the investigator Polres Kota Solok provide legal understanding to the victim's child's family first. Thirdly, unlike the perception of law enforcement officers, regular coordination is required. Fourth, facilities and infrastructure in the area are still limited, so the government should try to equip all facilities and infrastructure needed for legal protection of children.